Gypsies and Romanians: shared history and cultural and linguistic ties (a contribution) - Cychnerski, Tomasz (Balcanica Posnaniensia. Acta et studia, 2001)
The article analyzes the centuries-long historical, cultural, and linguistic connections between the Roma and the Romanians, demonstrating the mutual influences that have shaped both communities over more than six hundred years. The author focuses on the impact of long-term coexistence on the development of Roma language, culture, and identity, as well as on transformations within Romanian folk culture. The aim of the study is to present the origins of the Roma presence in Romanian lands and to identify the most important consequences of their long-standing coexistence with the Romanian population. The research is based on a historical-linguistic method that draws upon findings from linguistics, historical sources, and analyses of migration processes. The author points out that Romania has for centuries been home to the largest Roma population in Europe, currently numbering approximately 1.5 million people. Although Roma lived as an unfree population for a substantial part of their history, they nevertheless succeeded in preserving their cultural and linguistic identity. Particular attention is devoted to the evolution of the Romani language, which was influenced by Persian, Armenian, Greek, and Romanian linguistic traditions. As a result, numerous dialects emerged, including the Kelderari and Lovari groups. The author emphasizes that the presence of a large Roma population also left a mark on Romanian folk culture and language. The conclusions indicate that Romanian–Roma relations constitute an example of long-term cultural exchange. This process resulted both in the preservation of Roma ethnic distinctiveness and in the mutual penetration of cultural elements from both communities, significantly influencing their development and contemporary character.